A study on food-medicine continuum among the non-institutionally trained siddha practitioners of Tiruvallur district, Tamil Nadu, India - S. Esakkimuthu; S. Sylvester Darvin; S. Mutheeswaran; M. Gabriel Paulraj; P. Pandikumar; S. Ignacimuthu; N. A. Al-Dhabi (BMC, 2018)
Abstract Background Medicinal properties of the food species are one of the poorly documented and important areas of ethnopharmacology. The present survey quantitatively documented the medicinal foods prescribed by the non-institutionally trained siddha practitioners of Tiruvallur district of Tamil Nadu. Methods Field work was carried out between December 2014 and April 2017 using a questionnaire. The illnesses mentioned by the informants were grouped as illness categories on the basis of emic perceptions. Sufficiency of sampling of this survey was assessed by plotting the cumulative number of UR and Shannon-Wiener's index. The indices such as informant consensus factor (FIC), Index of Agreement on Remedies (IAR), and Cultural Food Significance Index (CFSI) were calculated. Results This study documented 165 medicinal foods used by 82 non-institutionally trained siddha practitioners of Tiruvallur district, and 73.93% of these preparations were plant based. Among the animal taxa, 82.05% were represented by fish taxa. The illness category gastrointestinal ailments is the majorly cited illness category treated with plant-based formulations. The illness categories viz., gastrointestinal ailments, hemorrhoids, and neural ailments had high consensus under the group of plant-based medicinal foods. In animal-based medicinal foods, kapha ailments had gained 23.07% of UR. The illness categories such as bone fractures, male reproductive ailments, blood ailments, and anabolic had high FIC values. Conclusions Deeper studies on different dietary cultures of India may help to derive better interpretations on food-medicine continuum. This study identified some important claims such as the use of citron, pomegranate and Solanum americanum (gastrointestinal ailments), Abutilon indicum, onions and elephant foot yam (hemorrhoids), Boerhavia diffusa (urinary ailments), Moringa oleifera (anemia), Aloe vera (gynecological ailments), Eclipta prostrata (liver ailments), ivy gourd (diabetes), citron (hypertension), Centella asiatica (psychological ailments), spade nose shark (lactogogue), reticulate whipray (wheezing and bronchitis), Katelysia opima (impotence), Indian squid (anemia), and Indian oil sardine (anabolic). More studies on these claims will help identify novel functional foods to add to the field of medical nutrition therapy, with traditional brand identity. Robust studies on the documentation of the traditional knowledge on marine resources will yield a good database for various stakeholders and policy makers.